(untitled) (Journal of the Pakistan Medical Association, 2020)
Abstract Soft-tissue calcification is characterised by the deposit of calcium in the damaged collagen fibres. The pathology of the phenomenon is not fully known. Trauma, spinal cord injury and traumatic brain injury have been reported as possible risk factors. Hypertrophic calcification of medial collateral ligament can be post-traumatic with unexplained aetiology. It can restrict the normal range of joint motion, affecting performance of activities of daily living, resulting in disturbance of quality of life. It may be managed conservatively, but if unsuccessful, surgical removal of the calcification may be carried out. Here, we present a case of post-traumatic heterotrophic calcification of medial collateral ligament of knee joint and review of current literature. Keywords: Heterotrophic calcification, Lower extremity functional scale, medial collateral ligament, Continuous...